Robotics and Automation in Mechanical Engineering: Transforming Modern Manufacturing Systems - Niket Jalihal; S C Sajjan (International Journal of Manufacturing and Production Engineering, 2026)
Robotics and automation have significantly transformed mechanical engineering, particularly in manufacturing, precision assembly, and intelligent systems integration. With the advancement of sensors, control systems, artificial intelligence, and mechatronics, robotic systems are now capable of performing complex tasks with high accuracy, repeatability, and efficiency. This article explores the role of robotics in modern mechanical applications, including industrial automation, collaborative robots, predictive maintenance, and smart manufacturing. It also discusses design considerations, challenges, and future trends shaping the next generation of automated mechanical systems The integration of robotics into mechanical engineering has improved productivity and operational efficiency across various industries. Modern robotic systems are designed to perform repetitive and hazardous tasks that were traditionally carried out by humans. This not only reduces the risk of workplace injuries but also ensures consistent product quality and faster production cycles. Industries, such as automotive manufacturing, electronics assembly, aerospace production, and packaging rely heavily on robotic systems to maintain precision and reliability in large-scale operations Another important development in robotics is the emergence of collaborative robots, often referred to as cobots. Unlike traditional industrial robots that operate in isolated environments, cobots are designed to work safely alongside human workers. These systems are equipped with advanced sensors, machine vision, and safety mechanisms that allow them to detect human presence and adjust their movements accordingly. As a result, collaborative robots enhance flexibility in manufacturing environments and allow companies to combine human creativity with robotic precision Predictive maintenance has also become a key component of robotic automation. By using sensors and data analytics, robotic systems can monitor equipment conditions in real time and identify potential failures before they occur. This capability reduces unexpected downtime, lowers maintenance costs, and improves overall system reliability. The use of artificial intelligence and machine learning further enhances the ability of robots to analyze operational data and optimize performance.
Keywords: Robotics; assembly; automations; robotic system; robotics in mechanical engineering; smart manufacturing